A CROSS-SECTIONAL STUDY TO EVALUATE ACUTE KIDNEY INJURY IN SCRUB TYPHUS PATIENTS - pani, Shradhanjali; Sethi, Taranisen; kumarpatel, Nayan; majhi, chakradhar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study was conducted with the objective to estimate the incidence and severity of acute kidney injury (AKI) scrub typhus patients. Methods: This was a cross-sectional study conducted 90 patients diagnosed with scrub typhus in a tertiary care center. Basic demographic and treatment details of the patients were recorded. Routine hematological investigations and biochemical profiles were performed upon admission and follow-up. AKI was defined and classified based on the RIFLE criteria. Results: Mean age of the patients was 49.0±19.5 years and female preponderance was observed. The hemoglobin level was significantly lower in AKI patients as compared to non-AKI patients. Meanwhile, there was a significant increase in mean TLC count, CRP, total bilirubin in AKI patients as compared to non-AKI patients. was significantly higher as compared to those without AKI. Increasing age, ICU admission, shock, urinary abnormalities, and mechanical ventilation were the factors significantly associated with AKI. Conclusion: AKI is a frequently reported complication in scrub typhus patients. In evaluating febrile illness associated with AKI, scrub typhus should be considered.